Cooling System Maintenance of Sea Water in Supporting Performance of the Main Engine on SV. Servewell Vigor - Gilang Ramadhan Perwira Wibawa; Abdurohman; Ai Dewi Prihastuti (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The goal of the research is to learn more about the primary engine cooling system disruptions. It is anticipated that methods for managing and maintaining cooling water will enable the primary engine to run more efficiently. The author's research methodology will just employ descriptive techniques. By describing several variables related to issues and the unit under study among the phenomena under test, descriptive methods are a type of research that aims to present a comprehensive picture of a social setting or is intended for exploration and clarification of a phenomenon or social reality. According to the study's findings, the author only addresses two of the variables that can disrupt the seawater cooling circulation system.